Structural analysis of NGVM pressure regulator via FEA - Mohsin, R.; Nasri, N. S.; Kefly, F. (Faculty of Chemical Engineering & Natural Resources, 2008)
Rapid expansion of gas industries in Malaysia requires significant efforts towards development of NGV system which will bring about some economic improvements. In this particular project the study will focus upon the finite analysis of a ISI-stage pressure regulator for natural gas vehiclemotorcycle (NGVM). The objective of the study is to optimize design structure using a dedicated finite element analysis (FEA) applied with the most locally suitable available materials. This research is focused upon the development of pressure regulator system for Natural Gas VehicleMotorcycle (NGVM). The main objective is to optimize the designed prototype of NGVM pressure regulator via the assistance of finite element analysis (FEA). Only MODENAS KRISS IIOcc motorcycle with manual transmission will be used for testing purposes. Optimization of the structural design of the prototype will be carried out using FEA system known as NASTRAN/PATRAN. Through FEA calculation and simulation, analysis conducted could provide structural strength understanding of the prototype. Simulation and analysis of the NGVM body prototype also incorporate various types of body materials including stainless steel, brass and aluminium. Aluminium was found to provide the necessary strength with high strength capability. Further refinements of the structure incorporate the thickness optimization of the overall constructions.